Design and Synthesis of Small Molecules Based on a Substructural Analysis of the Histone Deacetylase Inhibitors TSA and SAHA - Lynda Ekou; Tchirioua Ekou; Javier Garcia; Isabelle Opalinski; Jean Pierre Gesson (E-Journal of Chemistry)
Inhibitors of histone deacetylases (HDACs) are patent inducers of differentiation and bear considerable potential as drugs for chemoprevention and treatment of cancer. In this paper, we have investigated three synthetic, inhibitors A1a,b, A2a. Analogue hybrid trichostatine A (TSA), suberoylanilide hydroxamic acid SAHA, in order to seek new histone deacetylases (HDACs) inhibitors.